Sulfur functionalization via epoxide ring opening on a reduced graphene oxide surface to form metal (II) Organo-bis-[1,2]-oxathiin - Kumar, Praveen; Bajpai, Himanshu; Gopinath, Chinnakonda S.; Luwang, Meitram Niraj (Inorganic Chemistry, 2022)
The epoxide ring-opening reaction in graphene oxide (GO) by nucleophiles is a very fascinating and advanced methodology to develop novel functional material. Herewith, we report an advanced strategy for opening the epoxide ring on the rGO surface via easily an available nucleophile (Na2S), which is further functionalized with O atom to obtain four-membered rings (FMRs). The Cd coordination with the S atom puts extra stress on the FMR leading to the C-C bond cleavage of the four-membered heteroatomic rings on the rGO surface. This strategic approach leads to the fabrication of an innovative metal organo-bis-[1,2]-oxathiin (MOBOT) chemical moiety (M = Cd, Zn). The MOBOT compound further shows enhanced H-2 generation activity and hence is promising as a potential photocatalyst for solar hydrogen generation. This compound might also be a potential candidate for optoelectronic applications.